(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2023)
Abstract The main problem of the study lies in the lack of a clear perception among the study sample about the impact of digital marketing tools on legal liquidity. Legal) of the International Development Bank for Investment and Finance and to achieve the objectives of the research, the method of observation and survey was used in measuring the dimensions of digital marketing. As for banking liquidity, the reports and financial statements of the bank were used as the research sample, as well as the use of the statistical analysis program SPSS in the statement of the relationship The study concluded, in summary, the following: Marketing tools are one of the main pillars of the modern way of competition in organizations in general and banks in particular, for the purpose of effective and frequent communication with customers and parties related to the bank, which encourages the bank to build marketing networks and develop modern and sophisticated tools and methods.The study also recommended a number of recommendations, the most important of which was that the Central Bank of Iraq should direct Iraqi private banks to prepare an annual plan for liquidity and for each bank for the purpose of using and employing cash liquidity in excess of the standard rate determined by the Central Bank, whether by lending it or investing it in other activities for the development of the national economy between the variables of the study.